Draft genome sequence of Mesotoga strain PhosAC3, a mesophilic member of the bacterial order Thermotogales, isolated from a digestor treating phosphogypsum in Tunisia. Issue 1 (December 2015) - Ben Hania, Wajdi; Fadhlaoui, Khaled; Brochier-Armanet, Céline; Persillon, Cécile; Postec, Anne; Hamdi, Moktar; Dolla, Alain; Ollivier, Bernard; Fardeau, Marie-Laure; Le Mer, Jean; Erauso, Gaël
Abstract Mesotoga strain PhosAc3 was the first mesophilic cultivated member of the orderThermotogales. This genus currently contain two described species, M. prima andM. infera . Strain PhosAc3, isolated from a Tunisian digestor treating phosphogypsum, is phylogenetically closely related toM. prima strain MesG1.Ag.4.2T . Strain PhosAc3 has a genome of 3.1 Mb with a G+C content of 45.2%. It contains 3, 051 protein-coding genes of which 74.6% have their best reciprocal BLAST hit in the genome of the type species, strain MesG1.Ag.4.2T . For this reason we propose to assign strain PhosAc3 as a novel ecotype of theMesotoga prima species. However, in contrast with theM. prima type strain, (i) it does not ferment sugars but uses them only in the presence of elemental sulfur as terminal electron acceptor, (ii) it produces only acetate and CO2 from sugars, whereas strain MesG1.Ag.4.2T produces acetate, butyrate, isobutyrate, isovalerate, 2-methyl-butyrate and (iii) sulfides are also end products of the elemental sulfur reduction in theses growth conditions.